Development and Validation of Chinese University Students’ Physical Activity Motivation Scale Under the Constraint of Physical Education Policies - Lin, Bo; Teo, Eng Wah; Yan, Tingting (Frontiers in Psychology, 2022)
Accurate measurement of university students’ motivation to engage in physical activity (PA) is vital towards developing better physical fitness programs. However, the types of motivation driven by government physical education policies were often excluded in current existing scales. This study aimed to redevelop and validate a new scale that incorporates the components of physical education policies to accurately measure Chinese University Students’ Physical Activity Motivation (CUSPAMS). A total of 641 university students (M = 20.23 years; SD = 1.46) who regularly participate in physical activities from five universities in China completed the online CUSPAMS. The initial exploratory factor analysis (EFA) (n = 311) yielded nine factors and explaining 67.03% of the variance. Subsequent confirmatory factor analysis (CFA) (n = 330) provided strong support for the 9-factor modela retaining 32 items, model fit index of x2/df = 2.359, CFI = .91, TLI = .89, RMSEA = .06 showed good construct validity. CUSPAMS also showed sufficient content validity, face validity, convergent validity, and item discriminant validity. Additionally, the overall Cronbach alpha reliability coefficient for CUSPAMS was .90, while reliability coefficients for individual factors ranged from .60 to .88. In conclusion, CUSPAMS is a reliable new multi-dimensional scale to evaluate motivation for PA engagement for Chinese university students.